Studi Komparatif Mazhab Al-Syafi’i dan Mazhab Hanafi dalam Pengelolaan Makam: Studi Kasus Taman Makam Pahlawan Panaikang Kota Makassar - Rahman, Arif; Winanda (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2023)
Views of the Al-Syafi’i and Hanafi Schools About Tomb Management (Case Study of the Panaikang Heroes Cemetery in Makassar City)" with two problem formulations, namely: 1). How is the Management of the Cemetery at the Panaikang Heroes Cemetery?, 2). How is the Assessment of the Al-Syafi’I and Hanafi Schools on the Management of Tombs at the Panaikang Heroes Cemetery in Makassar City). This type of research is a field research type (Field Research.) The results of this study indicate that the views of the Shafi’i and Hanafi schools on the management of tombs both agree that the shape of the tomb building must deepen the excavation of the tomb, and the length and breadth of approx. follow the corpse. Raise the mound of earth to the size of an inch from the ground, so that it is known that it is a tomb. Don’t build graves, build buildings over graves, don’t build graves in mosques, it’s makruh to make the graves good if there are things that bring goodness. While the graves in Islam are generally only rectangular in shape, accompanied by stones that signify the tombs of men and women, which are single for men and even for women. In addition, the tomb building is also accompanied by a mound of earth that is no more and no less than an inch. It is hoped that the government of the Makassar City Environment Service as a facilitator is more effective in managing funerals properly, the community, and as a regulator the government is expected to be more progressive in making regulations that clear in managing the burial grounds of each area.